2007
DOI: 10.1093/aje/kwm277
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Deprivation and Preterm Birth among Non-Hispanic Black and White Women in Eight Geographic Areas in the United States

Abstract: Disparities in preterm birth by race and ethnic group have been demonstrated in the United States. Recent research has focused on the impact of neighborhood context on racial disparities in pregnancy outcomes. The authors utilized vital-record birth certificate data and US Census data from eight geographic areas in four states (Maryland, Michigan, North Carolina, and Pennsylvania) to examine the relation between neighborhood deprivation and preterm birth among non-Hispanic White and Black women. The years cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
193
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(208 citation statements)
references
References 30 publications
12
193
0
3
Order By: Relevance
“…At the contextual level, recent studies have found that more disadvantaged neighborhoods, measured in terms of poverty, 6 unemployment, 7 income, 8 compound deprivation index, 9 or violent crime rate, 10 have higher prevalence of adverse pregnancy outcomes; also, mothers residing in such neighborhoods have higher individual risk of presenting an adverse pregnancy outcome. 11,12 Neighborhood socioeconomic level is the result of macro-level structural factors including economic aspects, migration, discrimination, political decisions, and public policies 13 thus constituting a key area of health inequalities research. 14 In Spain, immigration (from developing countries) is a fairly recent phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…At the contextual level, recent studies have found that more disadvantaged neighborhoods, measured in terms of poverty, 6 unemployment, 7 income, 8 compound deprivation index, 9 or violent crime rate, 10 have higher prevalence of adverse pregnancy outcomes; also, mothers residing in such neighborhoods have higher individual risk of presenting an adverse pregnancy outcome. 11,12 Neighborhood socioeconomic level is the result of macro-level structural factors including economic aspects, migration, discrimination, political decisions, and public policies 13 thus constituting a key area of health inequalities research. 14 In Spain, immigration (from developing countries) is a fairly recent phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Our results overall do not support the positive findings from some previous studies that assessed preterm birth in relation to neighborhood deprivation as a summary variable among AfricanAmerican women in different geographic regions. [16][17][18][19] O'Campo et al 16 presented a summary odds ratio of 1.15 (95 % CI, 1.08, 1.23) for Non-Hispanic Black women comparing the highest versus lowest quintile of neighborhood deprivation using data from four states. The authors also examined effect estimates for Non-Hispanic Black women across eight study areas and reported that six of the eight area-specific odds ratios, ranging from 0.88 to 1.40, were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several studies have examined the association of neighborhood socioeconomic characteristics with preterm birth. [9][10][11][12][13][14][15][16][17][18][19] All except one 14 found statistically significant associations with at least one neighborhood-level indicator after adjustment for individual-level factors. Although many studies have assessed neighborhood characteristics as single variables, [9][10][11][12][13][14][15] the complexities of neighborhood SES may be better captured by a summary variable comprised of multiple area-level factors.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In general, poverty indices measure the proportion of families within a defined geographical unit with a combination of circumstances indicating fewer resources or a great need of basic services, or both. 2 Different studies have studied familiar and regional adverse social determinants in relation to perinatal outcome, such as neonatal mortality, 3 low birth weight 4 and prematurity, 5 but not in relation to congenital anomalies. Among the few reported causes on this issue, a low maternal socioeconomic level (SEL) has been associated with a higher risk of having a newborn infant with cleft lip, 6,9 neural tube defects, 7 and heart diseases.…”
Section: Introductionmentioning
confidence: 99%